CFD-Based PSO Optimization of Bamboo Roof Trusses Under Wind Loading - Nurwin Adam G. Muhammad; Jerson N. Orejudos; Mary Joanne C. Aniñon; Lessandro Estelito O. Garciano (Civil Engineering Journal, 2026)
Bamboo roof trusses are promising for low-carbon housing, but their performance under strong wind is highly influenced by roof geometry. This study developed a coupled computational fluid dynamics (CFD) and particle swarm optimization (PSO) framework to optimize a bamboo Howe roof truss under extreme wind loading. The objective was to reduce the maximum member utilization by finding a roof-truss geometry that responds efficiently to geometry dependent wind effects. For each candidate geometry, ANSYS SpaceClaim and ANSYS Fluent were used to update the roof profile and compute the wind-induced force resultants acting on the roof surfaces. These force resultants, together with roof and ceiling dead loads, were then applied to a MATLAB two-dimensional frame model to calculate member forces, deflections, and utilization ratios. The PSO run converged after 660 objective-function evaluations over 22 iterations using 30 particles per iteration. The optimized truss had a ridge height of hr = 2.079 m, r1 = 0.324, and r2 = 0.487, giving a maximum member utilization of 0.116, small deflection, and a truss volume of approximately 0.05 m³. Compared with the best solution in the first iteration, the optimized design reduced maximum utilization by 37%. The main contribution of this study is the integration of CFD derived wind loading with PSO-based bamboo truss optimization, allowing both wind demand and structural response to be updated during the search process.